2016
DOI: 10.1136/jim-2016-000092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12 Weeks of Atorvastatin Therapy on Myocardial Fibrosis and Circulating Fibrosis Biomarkers in Statin-NaïVe Patients with Hypertension with Atherosclerosis

Abstract: NTC00172419; results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
0
5
1
Order By: Relevance
“…McKinnon et al (46) showed that deletion of galectin-3 in the apolipoprotein E (−/−) knockout mice resulted in a markedly reduced volume of atherosclerotic plaques, and the authors concluded that strategies that inhibit galectin-3 may be a new approach in the treatment of atherosclerotic diseases. In a small study, 15 statin-naive patients with atherosclerosis were given atorvastatin 40 mg/day for 12 weeks, and at the end of study, galectin-3 levels decreased non-significantly (47). But in our study, atorvastatin 80 mg/day seems to have no effects on galectin-3 levels in patients with AMI at the end of 4-week therapy.…”
Section: Discussioncontrasting
confidence: 73%
“…McKinnon et al (46) showed that deletion of galectin-3 in the apolipoprotein E (−/−) knockout mice resulted in a markedly reduced volume of atherosclerotic plaques, and the authors concluded that strategies that inhibit galectin-3 may be a new approach in the treatment of atherosclerotic diseases. In a small study, 15 statin-naive patients with atherosclerosis were given atorvastatin 40 mg/day for 12 weeks, and at the end of study, galectin-3 levels decreased non-significantly (47). But in our study, atorvastatin 80 mg/day seems to have no effects on galectin-3 levels in patients with AMI at the end of 4-week therapy.…”
Section: Discussioncontrasting
confidence: 73%
“…Hence, changes in treatment and progression of disease were not taken into account. It has been reported that statin, ACEI, and ARB have no significant effect on galectin‐3 levels, but there are so far no data on the effect of diabetes medications on galectin‐3 levels. Furthermore, since our hospital is a secondary/tertiary referral centre, our cohort of patients are likely to be more complex than those in the general population or primary care, and the relationship between serum galectin‐3 levels and adverse cardiovascular outcome may not be generalizable to other patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [4] demonstrated that Ato ameliorates radiation-induced cardiac fibrosis in Sprague-Dawley rats. Similarly, Chang et al [5] showed that medium-dose Ato treatment for 12 weeks resulted in a significant reduction in myocardial fibrosis in patients. However, the specific mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 96%